Arasarí Banana (Baillonius bailloni) muerto al depredar un nido de Carpintero Oliva Manchado (Veniliornis spilogaster) - López-Lanús, Bernabé; Rodríguez Goñi , Hernán (Nuestras Aves, 2004)
Este artículo no cuenta con un resumen.